2020 42nd Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2020
DOI: 10.1109/embc44109.2020.9176228
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Techniques to Improve Intraoperative Awareness Detection from Electroencephalographic Signals

Abstract: Every year, millions of patients regain consciousness during surgery and can potentially suffer from posttraumatic disorders. We recently showed that the detection of motor activity during a median nerve stimulation from electroencephalographic (EEG) signals could be used to alert the medical staff that a patient is waking up and trying to move under general anesthesia [1], [2]. In this work, we measure the accuracy and false positive rate in detecting motor imagery of several deep learning models (EEGNet, dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The difference between results of MI + MNS vs. MNS and MI vs. Rest paradigms was demonstrated earlier in [10], [23]. But previous investigations were done only for the 128 electrode setup.…”
Section: Comparing Paradigmsmentioning
confidence: 87%
See 1 more Smart Citation
“…The difference between results of MI + MNS vs. MNS and MI vs. Rest paradigms was demonstrated earlier in [10], [23]. But previous investigations were done only for the 128 electrode setup.…”
Section: Comparing Paradigmsmentioning
confidence: 87%
“…There are several deep learning architectures that already showed competitive results for MI vs. Rest task in BCI domain [20]- [22]. At the same time, we already showed potential of convolutional neural networks to classify MI + MNS vs. MNS task on the smaller dataset [23]. Also, one more challenge is to decrease number of EEG electrodes.…”
Section: Introductionmentioning
confidence: 95%
“…There has been a growing interest in deep learning methods for MI classification. A recent study ( Avilov et al, 2020 ) tested three deep learning methods, including DeepConvNet, ShallowConvNet, and EEGNet, to detect MI with Median Nerve Stimulation (MNS) versus MNS during rest to prevent Accidental Awareness during General Anesthesia. The authors demonstrated that the deep learning network EEGNet outperformed not only traditional classifiers like CSP-LDA and the minimum distance to Riemannian mean algorithm (MDRM), but the other two deep learning architectures as well.…”
Section: Methodsmentioning
confidence: 99%
“…In deep learning, a convolutional neural network (CNN) is a class of artificial neural network (ANN), most commonly applied to image and video recognition, recommender systems, image classification, image segmentation, medical image analysis, natural language processing, braincomputer interfaces, and financial time series [1][2][3][4][5][6][7][8][9][10]. CNNs are regularized versions of multilayer perceptrons.…”
Section: Deep Learningmentioning
confidence: 99%